Stan i potrzeby badań nad uzbrojeniem z okresu wczesnego średniowiecza na terenie Europy Środkowej - Głosek, Marian (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
Archaeological excavations and archaeological and architectural researches are the main material source of attaining new, often fragmented elements of armament. Simultaneously war time contributed to the liquidation of many interesting collections of armament from central Europe. Weapons uncovered by archaeologists are very often the main element allowing to date a given site, identify social status of its owner, define range of trade and technical advancement of a given community. Intensification of archaeological researches in Poland at early Mediaeval sites is connected with the 1000th anniversary of the Polish slate. Numerous finds of armament uncovered during excavations were a subject of scientific study of such archaeologists as: A. Nadolski, W. Sarnowska, Z. Hilczerówna-Kurnatowska, J. Żak, W. Szymański. On this bases a group of experts in armament emerged. Among them are: A. Nowakowski, L. Kajzer, M. Głosek, К. Wachowski, W. Świętosławski and L. Maćkowiak. In Ukraine and Byelorussia the researches devoted to armament are just beginning to grow. Such names as G. V. Laskavy, S. A. Pivovarcik, J. A. Zajac or A. Kraucevic should be mentioned here. The development of scientific research on armament seems to be in a better condition in Lithuania and Latvia. The works by V. Kazakevicius, J. Stankus, K. Gabrunajte, R. Volkaitć-Kulikauskienć or L. Vaitkunskiene, as well as A. Anteins and M. Atgazis deliver general information about early Mediaeval armament throughout the territory of these two countries. Researches on armament in the Czech and Slovakia territory of are much more developed. Such authors as A. Ruttkay, J. Vladâr, D. Bialakovâ, B. Kavânovâ, N. Profantovâ, D. Hejdovâ, J. Eisner, R. Pleiner, E. Wagner, Z. Drobna and J. Durdik have seriously contributed to the development of knowledge of armament in their countries. Hungarian experts at arms systematically deepen their knowledge about armament, particularly as far as the period of “homeland occupation” is concerned. The armament of Avars and Hunes has also occurred to be a very interesting subject of studies. However, the somewhat outdated monograph by J. Kalmâr is the only publication summing up the achievements of Hungarian experts at arms. The studies of L. Kovâcs are noteworthy as well. No important progress has been recently noticed in the German knowledge on armament at least in the territory of eastern part of the country. The works by H. Muller and H. Kölling, I. Heind, U. Schoknecht, L. Diemer seam to support the above conclusion. After the collapse of the former USSR, newly born states face great problems not only of financial nature. What they definitely need in order to form independent science is an exchange of achievements, experiences and literature as well as an aid of foreign specialists.